Legal Implications for PPAT Employees Serving as Instrumental Witnesses in Title Transfer Agreements - Amanda, Rizki; Tjempaka, Tjempaka (Magister Ilmu Hukum Fakultas Hukum Universitas 17 Agustus 1945 Surabaya, 2024)
Employees or instrumental witnesses of PPAT play a crucial role, particularly in service provision. Not only can Land Deed Officials be defendants, but employees or instrumental witnesses may also become defendants if there is a tort claim due to slow services causing harm to their clients. The presence of instrumental witnesses is vital as it can help maintain the safety of the PPAT's position in the event of contested deeds. The purpose of this study is to determine the legal consequences for PPAT employees who act as instrumental witnesses in title transfer agreements. This research employs a normative juridical method with a statutory approach and a conceptual approach. The findings of this study indicate that if an issue arises after the service is provided by the Land Deed Official to the client and involves employees or instrumental witnesses, the Land Deed Official must ensure the safety of their employees. PPAT employees who act as witnesses in title transfer agreements bear significant legal responsibilities, particularly if they are involved in unlawful acts. They may face legal liability under Article 1365 of the Indonesian Civil Code, which states that any unlawful act causing damage to another obliges the person who committed the act to compensate for the damage.